Fine-grained access control for cloud computing. (1st January 2013) - Ye, Xinfeng; Khoussainov, Bakh
Fine-grained access control schemes are commonly used in cloud computing. In this type of schemes, each data item is given its own access control policy. The entity that wants to access the data item needs to provide its credentials to a policy enforcer. In a cloud environment, normally, the policy enforcer is not the owner of the data. The access control policies and the credentials might reveal some information that the policy enforcer is not entitled to know. This paper proposes a fine-grained access control scheme. It prevents the policy enforcers from comprehending the access control policies and the entities' credentials by using cryptographic techniques. Compared with the existing schemes, the proposed scheme provides higher level privacy.